2011
DOI: 10.1371/journal.pone.0025899
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sample Handling on Cross Sectional HIV Incidence Testing Results

Abstract: Objective(s)To determine if mishandling prior to testing would make a sample from a chronically infected subject appear recently infected when tested by cross-sectional HIV incidence assays.MethodsSerum samples from 31 subjects with chronic HIV infection were tested. Samples were subjected to different handling conditions, including incubation at 4°C, 25°C and 37°C, for 1, 3, 7 or 15 days prior to testing. Samples were also subjected to 1,3, 7 and 15 freeze-thaw cycles prior to testing. Samples were tested usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…The key recent advance in cross-sectional HIV incidence estimation is the development, refinement, and validation of multiassay algorithms (MAAs) [28•,98••,99•,100•,101••,102,103•,104]. MAAs apply a sequential, hierarchical set of assays to classify confirmed seropositive samples into recent versus long-standing infection categories.…”
Section: Evolving Practice In Hiv Incidence Estimationmentioning
confidence: 99%
“…The key recent advance in cross-sectional HIV incidence estimation is the development, refinement, and validation of multiassay algorithms (MAAs) [28•,98••,99•,100•,101••,102,103•,104]. MAAs apply a sequential, hierarchical set of assays to classify confirmed seropositive samples into recent versus long-standing infection categories.…”
Section: Evolving Practice In Hiv Incidence Estimationmentioning
confidence: 99%
“…The method of assessing the avidity of the anti-HPV16 antibodies was previously reported. 19,20 We only evaluated HPV16 avidity because of the availability of particles for HPV16 for ELISA assays in our laboratory. In addition, the lower neutralization titers for the cross-related HPV types, would not allow a precise estimation for the ELISA-based avidity levels.…”
Section: Titers (Range Within Quartile) Controls N(%) Hpv58 Cases N(%mentioning
confidence: 99%
“…26 We previously demonstrated the stability of BED-CEIA results over time in a cohort of HIV-infected Ugandan women. 27 Interestingly, most men in the MACS also had stable BED-CEIA results over a period of several years (Fig. 1C) if they did not become virally suppressed (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…We recently demonstrated that repeated freeze thaws or prolonged incubation at various temperatures did not impact results obtained with the BED-CEIA; therefore, use of archived samples that may have been thawed previously was not likely to have led to artificially low BED-CEIA results in this study. 27 Studies are underway to determine whether persistent misclassification is explained by a viral factor (e.g., if the gp41 sequence in HIV from participants with persistently low BED-CEIA values differs significantly from the sequence of the peptide target in the BED-CEIA assay).…”
Section: Discussionmentioning
confidence: 99%